RNA-Seq and 16S rRNA Analysis Revealed the Effect of Deltamethrin on Channel Catfish in the Early Stage of Acute Exposure - Yibin Yang; Xia Zhu; Ying Huang; Hongyu Zhang; Yongtao Liu; Ning Xu; Guihong Fu; Xiaohui Ai (Frontiers in Immunology, 2022)
Deltamethrin (Del) is a widely used pyrethroid insecticide and a dangerous material that has brought serious problems to the healthy breeding of aquatic animals. However, the toxicological mechanisms of Del on channel catfish remain unclear. In the present study, we exposed channel catfish to 0, 0.5, and 5 μg/L Del for 6 h, and analyzed the changes in histopathology, trunk kidney transcriptome, and intestinal microbiota composition. The pathological analyses showed that a high concentration of Del damaged the intestine and trunk kidney of channel catfish in the early stage. The transcriptome analysis detected 32 and 1837 differentially expressed genes (DEGs) in channel catfish trunk kidneys after exposure to 0.5 and 5 μg/L Del, respectively. Moreover, the KEGG pathway and GO enrichment analyses showed that the apoptosis signaling pathway was significantly enriched, and apoptosis-related DEGs, including cathepsin L, p53, Bax, and caspase-3, were also detected. These results suggested that apoptosis occurs in the trunk kidney of channel catfish in the early stage of acute exposure to Del. We also detected some DEGs and signaling pathways related to immunity and drug metabolism, indicating that early exposure to Del can lead to immunotoxicity and metabolic disorder of channel catfish, which increases the risk of pathogenic infections and energy metabolism disorders. Additionally, 16S rRNA gene sequencing showed that the composition of the intestinal microbiome significantly changed in channel catfish treated with Del. At the phylum level, the abundance of Firmicutes, Fusobacteria, and Actinobacteria significantly decreased in the early stage of Del exposure. At the genus level, the abundance of Romboutsia, Lactobacillus, and Cetobacterium decreased after Del exposure. Overall, early exposure to Del can lead to tissue damage, metabolic disorder, immunotoxicity, and apoptosis in channel catfish, and affect the composition of its intestinal microbiota. Herein, we clarified the toxic effects of Del on channel catfish in the early stage of exposure and explored why fish under Del stress are more vulnerable to microbial infections and slow growth.